Case Report: Bow Hunter's Syndrome Caused by Compression of Extracranially Originated Posterior Inferior Cerebellar Artery - Enomoto, Noriya; Yagi, Kenji; Matsubara, Shunji; Uno, Masaaki (Frontiers in Neurology, 2021)
Bow hunter’s syndrome (BHS) is most commonly caused by compression of the vertebral artery (VA). It has not been known to occur due to an extracranially originated posterior inferior cerebellar artery (PICA), the first case of which we present herein. A 71-year-old man presented with reproducible dizziness on leftward head rotation, indicative of bow hunter’s syndrome. On radiographic examination, the bilateral VAs merged into the basilar artery, and the left VA was predominant. The right posterior inferior cerebellar artery (PICA) originated extracranially from the right VA at the atlas-axis level and ran vertically into the spinal canal. During the head rotation that induced dizziness, the right PICA was occluded and a VA stenosis was revealed. Occlusion of the PICA was considered to be the primary cause of the dizziness. The patient underwent surgery to decompress the right PICA and VA via a posterior cervical approach. Following surgery, the patient’s dizziness disappeared and the stenotic change at the right VA and PICA improved. The PICA could be a causative artery for BHS when it originates extracranially at the atlas-axis level, and posterior decompression is an effective way to treat it.